Difference between revisions of "2018 AMC 12A Problems/Problem 14"
MRENTHUSIASM (talk | contribs) (Sol 6 is quite similar to the solutions above, so I decide to delete it. Let me know if anyone is unhappy about it ...) |
MRENTHUSIASM (talk | contribs) m (→Solution 5 (Exponential Form)) |
||
(7 intermediate revisions by the same user not shown) | |||
Line 19: | Line 19: | ||
<cmath>\begin{align*} | <cmath>\begin{align*} | ||
\log_2{\left[(3x)^3\right]}&=\log_2{\left[(2x)^2\right]} \\ | \log_2{\left[(3x)^3\right]}&=\log_2{\left[(2x)^2\right]} \\ | ||
− | (3x)^3&=(2x)^2\\ | + | (3x)^3&=(2x)^2 \\ |
27x^3&=4x^2 \\ | 27x^3&=4x^2 \\ | ||
x&=\frac{4}{27}, | x&=\frac{4}{27}, | ||
Line 30: | Line 30: | ||
==Solution 2== | ==Solution 2== | ||
+ | We will apply the following logarithmic identity: | ||
+ | <cmath>\log_{p^n}{\left(q^n\right)}=\log_{p}{q},</cmath> | ||
+ | which can be proven by the Change of Base Formula: <cmath>\log_{p^n}{\left(q^n\right)}=\frac{\log_{p}{\left(q^n\right)}}{\log_{p}{\left(p^n\right)}}=\frac{n\log_{p}{q}}{n}=\log_{p}{q}.</cmath> | ||
+ | We rewrite the original equation as <math>\log_{(3x)^3} 64 = \log_{(2x)^2} 64,</math> from which | ||
+ | <cmath>\begin{align*} | ||
+ | (3x)^3&=(2x)^2 \\ | ||
+ | 27x^3&=4x^2 \\ | ||
+ | x&=\frac{4}{27}. | ||
+ | \end{align*}</cmath> | ||
+ | Therefore, the answer is <math>4+27=\boxed{\textbf{(D) } 31}.</math> | ||
+ | |||
+ | ~MRENTHUSIASM | ||
+ | |||
+ | ==Solution 3== | ||
By the logarithmic identity <math>n\log_b{a}=\log_b{\left(a^n\right)},</math> the original equation becomes <cmath>2\log_{3x} 2 = 3\log_{2x} 2.</cmath> | By the logarithmic identity <math>n\log_b{a}=\log_b{\left(a^n\right)},</math> the original equation becomes <cmath>2\log_{3x} 2 = 3\log_{2x} 2.</cmath> | ||
By the logarithmic identity <math>\log_b{a}\cdot\log_a{b}=1,</math> we multiply both sides by <math>\log_2{(2x)},</math> then apply the Change of Base Formula to the left side: | By the logarithmic identity <math>\log_b{a}\cdot\log_a{b}=1,</math> we multiply both sides by <math>\log_2{(2x)},</math> then apply the Change of Base Formula to the left side: | ||
Line 38: | Line 52: | ||
2\left[\log_{3x}{(2x)}\right] &= 3 \\ | 2\left[\log_{3x}{(2x)}\right] &= 3 \\ | ||
\log_{3x}{\left[(2x)^2\right]} &= 3 \\ | \log_{3x}{\left[(2x)^2\right]} &= 3 \\ | ||
− | (3x)^3&=(2x)^2\\ | + | (3x)^3&=(2x)^2 \\ |
27x^3&=4x^2 \\ | 27x^3&=4x^2 \\ | ||
x&=\frac{4}{27}. | x&=\frac{4}{27}. | ||
Line 70: | Line 84: | ||
~MRENTHUSIASM (Reformatting) | ~MRENTHUSIASM (Reformatting) | ||
− | ==Solution 5== | + | ==Solution 5 (Exponential Form)== |
− | + | Let <math>y=\log_{3x} 4 = \log_{2x} 8.</math> We convert the equations with <math>y</math> to the exponential form: | |
− | |||
<cmath>\begin{align*} | <cmath>\begin{align*} | ||
− | \ | + | (3x)^y&=4, \\ |
− | (3x)^ | + | (2x)^y&=8. |
+ | \end{align*}</cmath> | ||
+ | Cubing the first equation and squaring the second equation, we have | ||
+ | <cmath>\begin{align*} | ||
+ | (3x)^{3y}&=64, \\ | ||
+ | (2x)^{2y}&=64. | ||
+ | \end{align*}</cmath> | ||
+ | Applying the Transitive Property, we get | ||
+ | <cmath>\begin{align*} | ||
+ | (3x)^{3y}&=(2x)^{2y} \\ | ||
+ | (3x)^3&=(2x)^2 \\ | ||
27x^3&=4x^2 \\ | 27x^3&=4x^2 \\ | ||
x&=\frac{4}{27}, | x&=\frac{4}{27}, | ||
Line 81: | Line 104: | ||
from which the answer is <math>4+27=\boxed{\textbf{(D) } 31}.</math> | from which the answer is <math>4+27=\boxed{\textbf{(D) } 31}.</math> | ||
− | + | ~MRENTHUSIASM | |
− | |||
− | ~MRENTHUSIASM | ||
==See Also== | ==See Also== | ||
{{AMC12 box|year=2018|ab=A|num-b=13|num-a=15}} | {{AMC12 box|year=2018|ab=A|num-b=13|num-a=15}} | ||
{{MAA Notice}} | {{MAA Notice}} |
Latest revision as of 21:32, 15 August 2021
Contents
Problem
The solutions to the equation , where is a positive real number other than or , can be written as where and are relatively prime positive integers. What is ?
Solution 1
We apply the Change of Base Formula, then rearrange: By the logarithmic identity it follows that from which the answer is
~jeremylu (Fundamental Logic)
~MRENTHUSIASM (Reconstruction)
Solution 2
We will apply the following logarithmic identity: which can be proven by the Change of Base Formula: We rewrite the original equation as from which Therefore, the answer is
~MRENTHUSIASM
Solution 3
By the logarithmic identity the original equation becomes By the logarithmic identity we multiply both sides by then apply the Change of Base Formula to the left side: Therefore, the answer is
~Pikachu13307 (Fundamental Logic)
~MRENTHUSIASM (Reconstruction)
Solution 4
We can convert both and into and respectively: Converting the bases of the right side, we get Dividing both sides by we get from which Expanding this equation gives Thus, we have from which the answer is
~lepetitmoulin (Solution)
~MRENTHUSIASM (Reformatting)
Solution 5 (Exponential Form)
Let We convert the equations with to the exponential form: Cubing the first equation and squaring the second equation, we have Applying the Transitive Property, we get from which the answer is
~MRENTHUSIASM
See Also
2018 AMC 12A (Problems • Answer Key • Resources) | |
Preceded by Problem 13 |
Followed by Problem 15 |
1 • 2 • 3 • 4 • 5 • 6 • 7 • 8 • 9 • 10 • 11 • 12 • 13 • 14 • 15 • 16 • 17 • 18 • 19 • 20 • 21 • 22 • 23 • 24 • 25 | |
All AMC 12 Problems and Solutions |
The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions.